A method for preparing a fully aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding
Through a co-spinning wire preparing hyperlifted polyester-polysthenylene ether functional and all-aromatic LCD polyester fiber, the problem of poor compatibility of PPO resin and matrix materials, and improved the peeling strength and mechanical performance of the PCB copper plate.
Patent Information
- Application Number
- CN202211127190.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The compatibility of PPO resin with matrix fabric or fabric-free materials is poor, resulting in insufficient peel strength of the prepared PCB copper clad plate, affecting the processing and use quality.
By hybridization of over-lipid polyester-polystyrene function, maternal grains and conventional spinning-grade all-aromatic liquid crystal polyester co-spinning wires, prepare all-aromatic liquid crystal polyester fiber with high liquidity and low melt viscosity The resin is on the surface of the fiber to improve the compatibility of PPO resin and matrix materials.
Improved the peeling strength of PPO resin composite materials, improved the mechanical properties of PCB copper -covering plates, while maintaining the original performance of LCD polyester fibers, reducing the addition of functional aids.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a fully aromatic liquid crystal polyester and a preparation method of its fiber which are beneficial to PPO resin compounding, and belongs to the field of polymer materials and the field of semiconductors. Background Art
[0002] Conventional copper clad laminate (PCB) is made of electronic glass fiber cloth and other reinforcing materials impregnated in relevant resins, which are dried, cut, and stacked into base materials, and then pressed with copper foil through a hot pressing process to form a printed copper clad PCB circuit board, which plays the role of interconnection, support and insulation in electronic equipment.
[0003] However, with the miniaturization and high performance of electronic equipment components and the advent of the 5G era, the requirements for copper-clad circuit boards (PCBs) in this field are also rapidly developing towards high density, high precision and high performance. The main indicators used to evaluate the performance of copper-clad PCBs are the two key indicators of dielectric constant Dk and dielectric loss factor Df. The smaller and more stable Dk and Df are, the better the signal transmission performance of high-frequency and high-speed PCB substrates. In addition, higher requirements are also placed on the heat resistance, mechanical properties and flame retardant properties of PCB copper-clad boards.
[0004] Traditional PCB uses glass fiber cloth as reinforcement material, and its DK is about 6 to 7, which can no longer meet the high-frequency and high-speed requirements of 5G. Fortunately, after the exploration and efforts of countless experts and scholars in this field in recent years, a series of PCB copper-clad board materials that meet the high-frequency and high-speed requirements of the 5G era have been prepared by using LCP liquid crystal polyester materials with high strength, high heat resistance, high frequency and low dielectric loss as base fabrics or non-fabricated fabrics and copper foil composites.
[0005] In addition, PPO resin has been extensively studied by numerous experts and scholars as a curing layer for high-frequency and high-speed PCB copper-clad laminates due to its extremely low and stable dielectric constant and dielectric loss performance. However, due to the poor compatibility of polyphenylene ether with matrix materials such as glass fiber, organic fiber fabric or non-woven fabric, the peel strength of the PCB copper-clad laminate prepared by it is relatively insufficient, and even interlayer delamination damage occurs, which will eventually seriously affect the processing and use quality of the circuit board. Therefore, solving the compatibility problem of PPO resin with matrix fabric or non-woven material is the main problem affecting its application in the field of high-frequency and high-speed PCB copper-clad laminates.
[0006] For example, patent CN202110418357.1 discloses a low-dielectric and high-strength resin composition, which is characterized in that a cross-linking reaction between a functionalized cross-linked polyphenylene ether resin and a thermoplastic resin polymer with a benzene ring structure is used to form a cross-linked network interlaced structure between glass fiber matrix materials, which effectively avoids the problem of phase separation caused by the use of different resin polymers in traditional schemes. However, due to the large amount of high dielectric constant substances such as cross-linking curing agents and thermoplastic resin polymers in the system, the dielectric properties of the PPO resin itself are affected, so that the comprehensive dielectric constant of the finally prepared PCB copper clad laminate is above 3.4. At the same time, due to the existence of the cross-linking reaction, the complexity of the impregnation process of the composition containing the functionalized cross-linked polyphenylene ether resin and the matrix glass fiber cloth is greatly improved, which greatly reduces the production efficiency and increases the preparation cost.
[0007] In view of this, the invention team of this case conducted long-term research and exploration on the above-mentioned existing problems, and thus this case came into being. Summary of the invention
[0008] The object of the present invention is to provide a method for preparing a fully aromatic liquid crystal polyester and its fiber which are beneficial to PPO resin compounding. The fully aromatic liquid crystal polyester and its fiber which are beneficial to PPO resin compounding of the present invention are prepared by blending and spinning a hyperbranched polyester-polyphenylene ether masterbatch having high fluidity and excellent compatibility with conventional LCP liquid crystal polyester and conventional fiber-grade LCP resin, wherein the mass percentage of the branched polyester-polyphenylene ether functional masterbatch is 3% to 15%.
[0009] The objectives of the present invention are achieved through the following technical solutions.
[0010] A fully aromatic liquid crystal polyester and its fiber which are beneficial to PPO resin compounding are prepared from the following raw materials in percentage by weight:
[0011] Conventional spinning grade LCP resin: 85-97%;
[0012] Hyperbranched polyester-polyphenylene ether functional masterbatch: 3-15%.
[0013] Wherein, the conventional spinning-grade LCP (wholly aromatic liquid crystal resin) is a polyester resin showing liquid crystal properties in a molten state. The melt viscosity of the liquid crystal polyester used in the present invention is 20 to 100 Pa×S, preferably 30 to 60 Pa×S, and the DSC melting temperature ranges from 250°C to 350°C, preferably 280 to 335°C. Specifically, it is composed of two or more combinations of aromatic polyacids, aromatic hydroxycarboxylic acids and aromatic polyols as polymerization monomers. The aromatic polyacids and aromatic hydroxycarboxylic acids are aromatic diacids or aromatic hydroxycarboxylic acid compounds such as terephthalic acid, p-hydroxybenzoic acid, 6-hydroxy-2-naphthalenebenzoic acid, 2,6-naphthalene dicarboxylic acid, isophthalic acid, etc., and the aromatic polyol repeating unit is an aromatic diol compound such as 2,6-naphthalene diol, 4.4-dihydroxybiphenyl, hydroquinone, etc.
[0014] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared by stepwise polymerization reaction in a reactor under nitrogen protection from terminal phenolic hydroxyl polyphenylene ether, terephthalic acid PTA, ethylene glycol EG, trimesic acid or pyromellitic acid, a catalyst, and a heat stabilizer; based on the total mass of terephthalic acid and ethylene glycol, each component is prepared in the following amounts:
[0015]
[0016] The polymerization equation of the hyperbranched polyester-polyphenylene ether functional masterbatch is as follows:
[0017]
[0018] The terminal hydroxyl polyphenylene ether is a polyphenylene ether with phenolic hydroxyl groups at both ends, as shown in the chemical molecular formula of MPPO, with a number average molecular weight of 1000 to 50000, wherein X1, X2, X3, and X4 can be hydrogen atoms, halogens, alkyl groups and other functional groups but are not limited to the above functional groups, wherein X1, X2, X3, and X4 are preferably H atoms, R1 and R2 can be alkyl groups, hydrogen atoms, halogens, phenolic hydroxyl groups or alkoxy groups, but are not limited to the above functional groups, and preferably R1 and R2 are alkyl methyl groups.
[0019] The catalyst is a titanium catalyst or an antimony catalyst such as titanium glycolate, tetrabutyl titanate or antimony trioxide, antimony glycolate, antimony acetate or a mixture thereof.
[0020] The heat stabilizer is one or a mixture of alkyl phosphate, trimethyl phosphate and phosphite.
[0021] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0022] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0023] Since different types of diols or other types of polyhydroxy alcohols have different reactivity with carboxylic acid groups, after a large number of polymerization routes and process verifications, it is preferred that after the esterification reaction of terephthalic acid PTA, isophthalic acid or pyromellitic acid and ethylene glycol EG is completed, the terminal hydroxyl polyphenylene ether is added to the reactor for ester exchange reaction, and after the ester exchange reaction is completed, the polycondensation reaction stage is entered, and finally the hyperbranched polyester-polyphenylene ether functional masterbatch is obtained by the polycondensation reaction. The specific preparation process route is as follows Figure 1 shown.
[0024] The main reaction equation is as follows (Note: Since the step-by-step polymerization reaction is a reaction process in which multiple monomers and multiple intermediates are produced simultaneously, only several main and representative reaction processes in the reaction process are listed below. Those skilled in the art may make various changes or modifications thereto, and these equivalent forms also fall within the scope defined by the claims attached to this application):
[0025] (4) Esterification reaction
[0026]
[0027] (5) Transesterification reaction
[0028]
[0029] (6) Polycondensation
[0030]
[0031] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared according to the above preparation process in an 80L polyester polymerization reactor according to the following preparation process. The specific preparation process is as follows:
[0032] Esterification stage: Terephthalic acid PTA, isophthalic acid or pyromellitic acid and ethylene glycol EG are weighed according to the acid-alcohol molar ratio of 1:1.3-1.5, and are put into the reactor together with the catalyst and the heat stabilizer to carry out the esterification reaction under nitrogen protection. The reaction conditions are: reaction temperature 230-250°C, pressure 0.25-0.4Mpa, and the temperature at the top of the distillation column is controlled at 110-135°C. The reaction ends when the water output reaches 93-95% of the theoretical water output, and the pressure is released to prepare for the ester exchange stage.
[0033] Ester exchange stage: after the pressure of the reactor is released to normal pressure, the pre-weighed hydroxyl-terminated polyphenylene ether is put into the reactor, the pressure of the reactor is adjusted by filling with nitrogen, and the ester exchange reaction begins. The reaction temperature is 230-250°C, the pressure in the reactor is 0.25-0.4Mpa, and the temperature at the top of the fractionation column is 110-135°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to prepare for the polycondensation stage.
[0034] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 20-60Pa, and after the discharge power reaches the predetermined value (the stirring power setting value of the 80L reactor is 200W-250W), the polycondensation reaction ends, and the vacuum discharge is removed and granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0035] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method has the characteristics of high fluidity and low intrinsic viscosity due to its special spherical branched macromolecular structure. The melt viscosity of the prepared functional masterbatch is 3-20 Pa×S and the melting temperature is 210°C-260°C.
[0036] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0037] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a certain proportion after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0038] The drying temperature of polyester-polyphenylene ether masterbatch is 80℃~110℃, the vacuum degree is 10~30Pa, and the drying time is 12~24 hours; the drying temperature of aromatic LCP resin is 100℃~130℃, the vacuum degree is 10~30Pa, and the drying time is 8~12 hours.
[0039] Blended chip spinning process: spinning machine screw temperature 260 ~ 360 ℃, spinning die temperature 260 ~ 360 ℃, drafting roller temperature 70 ~ 120 ℃, spinning tunnel temperature 150 ~ 250 ℃, metering pump frequency 10 ~ 50HZ, spinning speed 500m / min ~ 2000m / min, drafting multiple 1.0 ~ 1.5 times.
[0040] The patent of the present invention provides a method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding. The method mainly comprises preparing a hyperbranched polyester-polyphenylene ether functional masterbatch with high fluidity and compatibility with a conventional spinning-grade wholly aromatic polyester LCP by twin-screw extrusion or single-screw blending spinning. When the prepared functional masterbatch with high fluidity and low melt viscosity is used in the blending spinning process with conventional aromatic polyester, when the polymer melt is extruded from the spinneret hole, due to the shearing effect of the spinneret wall on the spinning melt, the flow velocity of the melt in the spinneret produces a large velocity gradient in the vertical flow direction, causing the spinning melt to be stretched and deformed. When the spinning melt reaches the spinneret outlet, the external force on the melt molecular chain is instantly released, and the molecular chain stretched by shear returns to the curled state, thereby generating the so-called extrudate swelling phenomenon near the spinneret hole. At this time, the hyperbranched polyester-polyphenylene ether functional masterbatch at the spinneret hole will first quickly distribute to both sides of the melt due to its own low melt viscosity and high fluidity, thereby achieving the purpose of preferentially enriching the branched polyester-polyphenylene ether functional masterbatch resin on the fiber surface.
[0041] Compared with the prior art, the technical solution of the present invention has the following technical advantages:
[0042] (1) The present invention provides a method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to the composite of PPO resin. Starting from the design of macromolecular structure, a lot of efforts are invested in the exploration of polymerization route and process to prepare a new polyester-polyphenylene ether copolymer, also known as hyperbranched polyester-polyphenylene ether functional masterbatch. The polyester segment in the branched polyester-polyphenylene ether molecular structure gives the copolymer compatibility with aromatic polyester, while the polyphenylene ether segment gives the copolymer compatibility with polyphenylene ether PPO resin. In addition, the special spherical branched macromolecular structure of the masterbatch itself gives the functional masterbatch ultra-high flowability and low melt viscosity. When the hyperbranched polyester-polyphenylene ether functional masterbatch is spun with conventional spinning-grade wholly aromatic polyester by twin-screw extrusion or single-screw blending, due to the low melt viscosity and high fluidity of the functional masterbatch itself, it will first quickly distribute to both sides of the melt at the spinneret position, thereby achieving the branched polyester-polyphenylene ether functional masterbatch resin preferentially enriched on the surface of the wholly aromatic liquid crystal polyester fiber, effectively improving the compatibility of the liquid crystal polyester fiber and the polyphenylene ether PPO resin, and improving the problem of insufficient peel strength of the PCB copper clad plate prepared therefrom.
[0043] (2) In view of the excellent properties of the prepared hyperbranched polyester-polyether functional masterbatch, the branched polyester-polyphenylene ether functional masterbatch resin is ultimately enriched on the surface of the wholly aromatic liquid crystal polyester fiber, while the interior of the fiber contains no or only a small amount of functional resin. Only a small amount of addition is needed to greatly improve the compatibility problem between the wholly aromatic liquid crystal polyester and the polyphenylene ether resin, thereby preserving the original mechanical, heat resistance and other properties of the liquid crystal polyester fiber to the greatest extent, and at the same time reducing the effect of the addition of functional additives on the spinnability of the liquid crystal polyester. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 It is a technical route for synthesizing hyperbranched polyester-polyphenylene ether copolymer masterbatch. DETAILED DESCRIPTION
[0045] Below in conjunction with specific embodiment, further elaborate content of the present invention.It should be emphasized that these embodiments are only used for further explanation of the present invention, and can not be interpreted as limiting the scope of protection of the present invention.In addition, it should be understood that after reading the content described in the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope limited by the appended claims of the application.
[0046] The conventional spinning-grade wholly aromatic polyester resin in the following embodiments is selected from the LCP280 spinning-grade LCP resin with a melting point of 280°C and a melt viscosity of 35 Pa×S prepared by Shanghai Pulite Chemical Co., Ltd. The synthetic monomer terminal hydroxyl polyphenyl ether is selected from the terminal hydroxyl polyphenyl ether prepared by Nantong Xingchen Synthetic Materials Co., Ltd., in which X1, X2, X3, and X4 are H atoms, R1 and R2 are alkylmethyl functional groups, and the number average molecular weight is 8000.
[0047] Example 1
[0048] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0049] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0050] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0051]
[0052] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0053] The catalyst is antimony glycol.
[0054] The heat stabilizer is phosphite.
[0055] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0056] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0057] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.15 kg of pyromellitic acid, 3 g of catalyst ethylene glycol antimony, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0058] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 4.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0059] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0060] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 18.7 Pa×S, and the melting temperature was 258°C.
[0061] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0062] The branched polyester-polyphenylene ether functional masterbatch prepared above and conventional spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester and its fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0063] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0064] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0065] The spinnability of the above-mentioned different spinning speeds and different proportions of resins was evaluated, and the tensile strength of the fully aromatic liquid crystal polyester fibers prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper-clad board and its peel strength and dielectric constant were tested.
[0066] Example 2
[0067] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0068] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0069] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0070]
[0071] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0072] The catalyst is antimony glycol.
[0073] The heat stabilizer is phosphite.
[0074] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0075] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0076] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.15 kg of pyromellitic acid, 3 g of catalyst ethylene glycol antimony, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0077] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 3.0 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0078] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0079] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for its intrinsic viscosity and melting temperature. The prepared functional masterbatch had a melt viscosity of 10.3 Pa×S and a melting temperature of 256°C.
[0080] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0081] The branched polyester-polyphenylene ether functional masterbatch prepared above and conventional spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0082] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0083] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0084] The spinnability of the above-mentioned different spinning speeds and different proportions of resins was evaluated, and the tensile strength of the fully aromatic liquid crystal polyester fibers prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper-clad board and its peel strength and dielectric constant were tested.
[0085] Example 3
[0086] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0087] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0088] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0089]
[0090] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0091] The catalyst is antimony glycol.
[0092] The heat stabilizer is phosphite.
[0093] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0094] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0095] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.15 kg of pyromellitic acid, 3 g of catalyst ethylene glycol antimony, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0096] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 1.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0097] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0098] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for its intrinsic viscosity and melting temperature. The prepared functional masterbatch had a melt viscosity of 6.2 Pa×S and a melting temperature of 260°C.
[0099] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0100] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester and its fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0101] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0102] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0103] The spinnability of the above-mentioned different spinning speeds and different proportions of resins was evaluated, and the tensile strength of the fully aromatic liquid crystal polyester fibers prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper-clad board and its peel strength and dielectric constant were tested.
[0104] Example 4
[0105] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0106] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0107] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0108]
[0109] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0110] The catalyst is antimony glycol.
[0111] The heat stabilizer is phosphite.
[0112] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0113] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0114] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.30 kg of pyromellitic acid, 3 g of catalyst antimony glycol, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0115] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 4.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0116] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0117] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 8.0 Pa×S, and the melting temperature was 248°C.
[0118] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0119] The branched polyester-polyphenylene ether functional masterbatch prepared above and conventional spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain blended modified chips, and then the blended modified chips are melt-spun by a single-screw and double-screw spinning machine to obtain fully aromatic polyester and its fiber that are conducive to PPO resin compounding. The specific process parameters are as follows:
[0120] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0121] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0122] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0123] Example 5
[0124] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0125] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0126] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0127]
[0128] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0129] The catalyst is antimony glycol.
[0130] The heat stabilizer is phosphite.
[0131] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0132] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0133] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.30 kg of pyromellitic acid, 3 g of catalyst antimony glycol, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0134] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 3.0 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0135] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0136] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 5.0 Pa×S, and the melting temperature was 251°C.
[0137] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0138] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0139] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0140] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0141] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0142] Example 6
[0143] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0144] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0145] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0146]
[0147] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0148] The catalyst is antimony glycol.
[0149] The heat stabilizer is phosphite.
[0150] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0151] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0152] Esterification stage: PTA, 15 kg of ethylene glycol EG, 0.30 kg of pyromellitic acid, 3 g of catalyst antimony glycol, and 45 g of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3 MPa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0153] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 1.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0154] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0155] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 3.4 Pa×S, and the melting temperature was 249°C.
[0156] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0157] The branched polyester-polyphenylene ether functional masterbatch prepared above and conventional spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0158] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0159] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0160] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0161] Example 7
[0162] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0163] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0164] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0165]
[0166] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0167] The catalyst is antimony glycol.
[0168] The heat stabilizer is phosphite.
[0169] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0170] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0171] Esterification stage: according to the alcohol-acid molar ratio of 1.4:1, terephthalic acid PTA and ethylene glycol EG 15Kg, 0.45 kg of pyromellitic acid, 3 grams of catalyst ethylene glycol antimony, and 45 grams of thermal stabilizer phosphite are put into a reactor together for esterification reaction under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3Mpa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0172] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 4.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0173] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0174] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 6.0 Pa×S, and the melting temperature was 212°C.
[0175] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0176] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified chip, and then the blended chip is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic polyester and its fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0177] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0178] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0179] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0180] Example 8
[0181] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0182] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0183] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0184]
[0185] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0186] The catalyst is antimony glycol.
[0187] The heat stabilizer is phosphite.
[0188] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0189] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0190] Esterification stage: according to the alcohol-acid molar ratio of 1.4:1, terephthalic acid PTA and ethylene glycol EG 15Kg, 0.45 kg of pyromellitic acid, 3 grams of catalyst ethylene glycol antimony, and 45 grams of thermal stabilizer phosphite are put into a reactor together for esterification reaction under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3Mpa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0191] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 3.0 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0192] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0193] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 4.0 Pa×S, and the melting temperature was 214°C.
[0194] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0195] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester and its fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0196] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0197] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0198] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0199] Example 9
[0200] A fully aromatic liquid crystal polyester and fiber thereof which are beneficial to PPO resin compounding are prepared by blending and spinning conventional spinning-grade fully aromatic liquid crystal LCP and prepared branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10, and 85:15.
[0201] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0202] The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0203]
[0204]
[0205] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0206] The catalyst is antimony glycol.
[0207] The heat stabilizer is phosphite.
[0208] The above-mentioned method for preparing a wholly aromatic liquid crystal polyester and its fiber which is beneficial to PPO resin compounding comprises the following preparation steps:
[0209] (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch
[0210] Esterification stage: according to the alcohol-acid molar ratio of 1.4:1, terephthalic acid PTA and ethylene glycol EG 15Kg, 0.45 kg of pyromellitic acid, 3 grams of catalyst ethylene glycol antimony, and 45 grams of thermal stabilizer phosphite are put into a reactor together for esterification reaction under nitrogen protection. The reaction conditions are: the reaction set temperature is 245°C, the set pressure is 0.3Mpa, the set temperature of the distillation column top is 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0211] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 1.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0212] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0213] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 3.1 Pa×S, and the melting temperature was 213°C.
[0214] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0215] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester and its fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0216] The drying setting temperature of polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0217] Blending modified chip spinning process: the processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning channel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0218] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0219] In order to form a comparison with the above-mentioned embodiment and better reflect the technical advantages of the invention scheme, the corresponding comparative example 1 directly uses the wholly aromatic liquid crystal polyester without adding the polyester-polyphenylene ether masterbatch of the present invention to directly carry out spinning processing according to the following process parameters and test and evaluate its spinnability and related properties. Comparative Example 2 uses the PPO resin directly added with the unmodified PCB copper clad plate solidified layer to carry out spinning, and test and evaluate its spinnability and related properties. Comparative Example 3 uses the non-branched polyester-polyphenylene ether masterbatch with different terminal phenolic hydroxyl content and the wholly aromatic liquid crystal polyester to carry out blending spinning and test and evaluate its spinnability and related properties.
[0220] Comparative Example 1
[0221] A conventional spinning-grade fully aromatic liquid crystal LCP resin with a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C was directly spun according to the following spinning process and its performance was tested.
[0222] The drying temperature of polyaromatic LCP resin is set at 110℃, the vacuum degree is set at 22Pa, and the drying time is set at 12 hours. Blending chip spinning process: The processing temperatures of the spinning machine screw zones 1 to 5 are set at 270℃, 285℃, 290℃, 300℃, 305℃, 305℃, respectively, the spinning die head is set at 305℃, the drafting roller is set at 85℃, the spinning tunnel is set at 170℃, the metering pump is set at 22HZ, the spinning speed is set at 1000m / min, 1500m / min, 1800m / min, and the drafting multiple is 1.25 times.
[0223] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0224] Comparative Example 2
[0225] The PPO masterbatch prepared by direct physical blending of PPO resin and conventional spinning-grade LCP resin was blended with a fully aromatic liquid crystal polyester for spinning, and its spinnability and related properties were tested and evaluated. The specific steps are as follows:
[0226] The invention is prepared by blending and spinning spinning-grade fully aromatic liquid crystal LCP and prepared PPO resin masterbatch in weight ratios of 97:3, 95:5, 90:10 and 85:15.
[0227] The PPO resin masterbatch is prepared from the following raw materials in parts by weight:
[0228] Spinning grade LCP resin: 70%
[0229] PPO resin: 30%
[0230] The spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0231] The PPO resin is a PPO resin used for the curing layer of conventional high-frequency and high-speed PCB copper-clad laminates.
[0232] The above-mentioned PPO resin composite fully aromatic liquid crystal polyester fiber and its preparation method include the following preparation steps:
[0233] (1) Preparation of PPO resin masterbatch
[0234] The spinning-grade LCP resin and PPO resin are mixed evenly in a premix according to weight, and then blended and extruded into granules using a twin-screw extruder;
[0235] The processing temperatures of zones I to X of the twin-screw extruder are 270°C, 285°C, 295°C, 295°C, 300°C, 300°C, 300°C, 305°C, 305°C, 305°C, respectively. The main screw speed is 500-550r / min, and the water tank temperature is 30°C-60°C.
[0236] (2) Preparation of fully aromatic liquid crystal polyester fibers:
[0237] The polyphenylene ether composite LCP resin masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin composite. The specific process parameters are as follows:
[0238] The drying temperature of PPO resin masterbatch is set at 110℃, the vacuum degree is set at 22Pa, and the drying time is set at 12 hours; the drying temperature of aromatic LCP resin is set at 110℃, the vacuum degree is set at 22Pa, and the drying time is set at 12 hours.
[0239] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0240] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the prepared wholly aromatic liquid crystal polyester fibers was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0241] Comparative Example 3
[0242] Unbranched polyester-polyphenylene ether masterbatch with different terminal phenolic hydroxyl content was blended with conventional spinning-grade fully aromatic liquid crystal polyester for spinning, and its spinnability and related properties were tested and evaluated. The specific operation steps are as follows:
[0243] The invention is prepared by blending and spinning spinning-grade fully aromatic liquid crystal LCP and prepared non-branched polyester-polyphenylene ether functional masterbatch in weight ratios of 97:3, 95:5, 90:10 and 85:15.
[0244] The conventional spinning-grade fully aromatic liquid crystal LCP has a melt viscosity of 35 Pa×S and a DSC melting temperature of 280°C.
[0245] The non-branched polyester-polyphenylene ether functional masterbatch is prepared from terminal phenolic hydroxyl polyphenylene ether using the following raw materials in parts by weight:
[0246]
[0247] The terminal hydroxyl polyphenyl ether is a commercially available terminal hydroxyl polyphenyl ether with a number average molecular weight of 8000, wherein X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl functional groups.
[0248] The catalyst is antimony glycol.
[0249] The heat stabilizer is phosphite.
[0250] The above-mentioned PPO composite fully aromatic liquid crystal polyester fiber and its preparation method include the following preparation steps:
[0251] (1) Preparation of unbranched polyester-polyphenylene ether functional masterbatch
[0252] Esterification stage: PTA and 15 kg of ethylene glycol EG, 3 grams of catalyst ethylene glycol antimony, and 45 grams of thermal stabilizer phosphite are put into a reactor according to the alcohol-acid molar ratio of 1.4:1, and the esterification reaction is carried out under nitrogen protection. The reaction conditions are: the reaction temperature is set at 245°C, the pressure is set at 0.3 MPa, the temperature at the top of the distillation column is set at 120°C, and when the reaction water output reaches 95% of the theoretical water output, the pressure is released to prepare for entering the ester exchange stage.
[0253] Ester exchange stage: after the pressure of the reactor is released to normal pressure, 1.5 kg of terminal phenolic hydroxyl polyphenyl ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the ester exchange reaction is started. The reaction temperature is set to 240°C, the pressure in the reactor is 0.3Mpa, and the temperature at the top of the distillation column is 120°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to enter the condensation stage.
[0254] Polycondensation stage: After the pressure of the reactor drops to normal pressure, start vacuuming for polycondensation reaction, the vacuum degree is 50Pa, the reaction setting temperature is 260℃, and the polycondensation reaction ends when the discharge power reaches 235W. The vacuum is removed and the material is granulated to prepare branched polyester-polyphenylene ether functional masterbatch.
[0255] The branched polyester-polyphenylene ether functional masterbatch prepared by the above method was tested for its intrinsic viscosity and melting temperature. The melt viscosity of the prepared functional masterbatch was 72 Pa×S, and the melting temperature was 260°C.
[0256] (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber:
[0257] The branched polyester-polyphenylene ether functional masterbatch prepared above and the spinning-grade fully aromatic LCP resin are mixed in a ratio of 97:3, 95:5, 90:10, and 85:15 after vacuum drying to obtain a blended modified chip, and then the blended modified chip is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic polyester and its fiber that is conducive to PPO resin compounding. The specific process parameters are as follows:
[0258] The drying setting temperature of non-branched polyester-polyphenylene ether masterbatch is 105°C, the vacuum degree is set to 22Pa, and the drying time is set to 16 hours; the drying setting temperature of aromatic LCP resin is 110°C, the vacuum degree is set to 22Pa, and the drying time is set to 12 hours.
[0259] Blended chip spinning process: The processing temperatures of spinning machine screw zones 1 to 5 are set to 270℃, 285℃, 290℃, 300℃, 305℃, 305℃ respectively, the spinning die head is set to 305℃, the drafting roller is set to 85℃, the spinning tunnel is set to 170℃, the metering pump is set to 22HZ, the spinning speeds are set to 1000m / min, 1500m / min, 1800m / min respectively, and the drafting multiple is 1.25 times.
[0260] The spinning states at the above different spinning speeds were evaluated and the tensile strength of the wholly aromatic liquid crystal polyester fibers prepared therefrom was tested. The fabric woven therefrom was used to prepare a PCB copper clad board and the peel strength and dielectric constant of the PCB were tested.
[0261] A series of polyester-polyphenylene ether functional masterbatches, wholly aromatic liquid crystal polyester fibers and fabrics woven therefrom prepared in the above Examples 1 to 9 and Comparative Examples 1 to 3 were prepared into PCB copper clad laminates, and performance tests were performed according to the following test standards and conditions. The test data are shown in Tables 1, 2 and 3.
[0262] Melt viscosity was measured using a capillary rheometer Ch2000 (Malvecn) with a capillary size of 0.5 mm and a shear rate of 1000 s. -1 The melt viscosity of the prepared functional masterbatch at 300°C was measured under the conditions of.
[0263] Melting point test: Differential scanning chromatograph DSC 8000 was used to test the melting point of the prepared functional masterbatch, with a heating rate of 10°C / min.
[0264] The fiber strength test was conducted according to the method described in JIS L1013:2010. The strength of the prepared LCP fiber monofilament was tested at a tensile speed of 50 mm / min. Each fiber was tested 30 times, and the arithmetic mean of the test results was taken.
[0265] The PCB peel strength test is carried out according to the IPC-TM-650 2.4.9 test method, and the recorded data is the smaller peel strength value between the two sides of the double-sided board.
[0266] The dielectric constant test was performed using an Agilent N5230A instrument with an SPDR fixture at a measurement frequency of 10 GHz.
[0267] The spinnability is evaluated mainly by evaluating the spinnability of the spinning resin at different spinning rates of 1000m / min, 1500m / min, and 1800m / min. If there is no broken or filamentary yarn in the spinning process and the spinning continuity is good, the spinnability is evaluated as good; if there are intermittent broken or filamentary yarns in the spinning process, but the spinning continuity is acceptable, the spinnability is evaluated as good; if there are broken or filamentary yarns very easily in the spinning process and the spinning continuity is poor, the spinnability is evaluated as poor.
[0268] Table 1 Performance test data of polyester-polyphenylene ether functional masterbatch prepared in Examples 1 to 9 and Comparative Example 3
[0269]
[0270] Table 2 Performance and spinnability evaluation of a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding in Examples 1 to 9 and Comparative Examples 1 to 3
[0271]
[0272]
[0273]
[0274] Note: The above-mentioned fiber tensile strength shows no data, which means that the spinning was not successful and there is no product data.
[0275] Table 3 Performance evaluation of PCB copper clad laminates prepared from modified wholly aromatic liquid crystal polyester fibers prepared in Examples 1 to 9 and Comparative Examples 1 to 3
[0276]
[0277]
[0278] Table 1 shows the melting point and melt viscosity test data of the polyester-polyphenylene ether copolymer masterbatch prepared in Examples 1 to 9 and Comparative Example 3. From the test data results, it can be seen that the melting point and melt viscosity of the prepared polyester-polyphenylene ether copolymer are greatly affected by the content of the terminal hydroxyl polyphenylene ether monomer and the branching degree of the copolymer (the higher the content of the branched product pyromellitic acid, the higher the branching degree of the copolymer). That is, the higher the content of the hydroxyl polyphenylene ether monomer, the greater its melt viscosity, and the higher the branching degree of the copolymer, the lower the melt viscosity. Once its melting point drops significantly, how to balance the melt viscosity of the copolymer masterbatch and the polymer melting point performance, screen out the optimal technical solution and further verify the inventive effect of the prepared polyester-polyphenylene ether copolymer masterbatch, the team of this solution conducted a systematic performance evaluation of the prepared functional masterbatch.
[0279] Table 2 shows the performance and spinnability evaluation results of wholly aromatic liquid crystal polyesters and their fibers for Examples 1 to 9 and Comparative Examples 1 to 3. By evaluating the spinnability of the prepared polyester-polyphenylene ether copolymer masterbatch and the mechanical properties of the wholly aromatic polyester fiber prepared therefrom, a masterbatch formula was screened out that simultaneously meets the requirements of good spinnability under 1500 m / min spinning conditions and the mechanical properties of the prepared fiber being greater than 6.5 cN / dtex.
[0280] In order to further lock in the optimal technical solution for this scheme, the research team of this technical solution conducted a PCB copper clad board peel strength and dielectric constant performance evaluation on the polyester-polyphenylene ether copolymer masterbatch that meets the spinning conditions of 1500m / min and has good spinnability and the strength of the prepared aromatic liquid crystal polyester fiber is greater than 6.5cN / dtex. The specific evaluation results are shown in Table 3.
[0281] Through the above systematic technical demonstration, the technical effect of the present invention is fully verified and the optimal technical solution in this embodiment of the invention is finally locked in as the technical solution in Example 5 in which the content of phenolic hydroxy polyphenylene ether monomer is 20%, the content of branched isomellitic acid is 2%, and the mixing ratio with fiber-grade LCP resin is 5%.
Claims
1. A fully aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding, characterized in that: It is prepared from the following raw materials in percentage by weight: Conventional spinning grade fully aromatic LCP liquid crystal polyester resin: 85-97%; Hyperbranched polyester-polyphenylene ether functional masterbatch: 3-15%; The prepared hyperbranched polyester-polyphenylene ether functional masterbatch and conventional spinning-grade fully aromatic LCP liquid crystal polyester resin are mixed in a certain proportion after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding; The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared by stepwise polymerization reaction of terminal phenolic hydroxyl polyphenylene ether, terephthalic acid PTA, ethylene glycol EG, isophthalic acid or pyromellitic acid, a catalyst, and a heat stabilizer in a reactor under nitrogen protection; based on the total mass of terephthalic acid and ethylene glycol, each component is prepared according to the following dosage: 10 ~ 30% of polyphenylene ether with terminal phenolic hydroxyl groups; Isophthalic acid or pyromellitic acid 1 ~ 3%; Catalyst 100 ~ 500ppm; Heat stabilizer 0.1 ~ 0.5%; Terephthalic acid and ethylene glycol remaining components; The catalyst is a titanium catalyst or an antimony catalyst.
2. A wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 1, characterized in that: The conventional spinning-grade fully aromatic LCP liquid crystal polyester resin is a polyester resin showing liquid crystal properties in a molten state. The liquid crystal polyester has a melt viscosity of 20-100 Pa×S and a DSC melting temperature range of 250°C-350°C.
3. A wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 2, characterized in that: The conventional spinning-grade fully aromatic LCP liquid crystal polyester resin is a polyester resin that exhibits liquid crystal properties in a molten state, the liquid crystal polyester melt viscosity is 30-60 Pa×S, and the DSC melting temperature range is 280-335°C; the conventional spinning-grade fully aromatic LCP liquid crystal polyester resin is prepared from one or more of aromatic polyacids, aromatic hydroxycarboxylic acids and aromatic polyols as polymerization monomers.
4. A wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 3, characterized in that: The aromatic polyacid and aromatic hydroxycarboxylic acid are terephthalic acid, p-hydroxybenzoic acid, 6-hydroxy-2-naphthalenebenzoic acid, 2,6-naphthalene dicarboxylic acid, and isophthalic acid; the aromatic polyol is 2,6-naphthalene diol, 4,4-dihydroxybiphenyl, and hydroquinone.
5. The wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 1, characterized in that: The polymerization equation of the hyperbranched polyester-polyphenylene ether functional masterbatch is as follows: ; or 。 6. A wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 5, characterized in that: The chemical formula of the MPPO is a hydroxy-terminated polyphenylene ether, which is a polyphenylene ether with a number average molecular weight of 1000 to 50000 and phenolic hydroxyl groups at both ends, wherein X1, X2, X3, and X4 are selected from hydrogen atoms, halogens, or alkyl functional groups; and R1 and R2 are selected from alkyl groups, hydrogen atoms, halogens, phenolic hydroxyl groups, or alkoxy groups.
7. A wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 6, characterized in that: The X1, X2, X3, and X4 are H atoms, and R1 and R2 are alkylmethyl groups.
8. The wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 1, characterized in that: The titanium catalyst is selected from titanium ethylene glycol, tetrabutyl titanate, or a mixture of two thereof; the antimony catalyst is selected from antimony trioxide, antimony ethylene glycol, antimony acetate, or a mixture thereof.
9. The wholly aromatic liquid crystal polyester fiber that is beneficial to PPO resin compounding according to claim 1, characterized in that: The heat stabilizer is one or a mixture of alkyl phosphate, trimethyl phosphate and phosphite.
10. The method for preparing a wholly aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding according to any one of claims 1 to 9, characterized in that: The method comprises the following preparation steps: (1) Preparation of hyperbranched polyester-polyphenylene ether functional masterbatch After the esterification reaction of terephthalic acid PTA, isophthalic acid or pyromellitic acid and ethylene glycol EG is completed, the hydroxy-terminated polyphenylene ether is added to the reactor for transesterification reaction. After the transesterification reaction is completed, the polycondensation reaction stage is entered, and finally the hyperbranched polyester-polyphenylene ether functional masterbatch is obtained through the polycondensation reaction; the reaction equation is as follows: a. Esterification reaction ; b. Transesterification ; c. Polycondensation ; The hyperbranched polyester-polyphenylene ether functional masterbatch is prepared according to the above preparation process in an 80L polyester polymerization reactor according to the following preparation process. The specific preparation process is as follows: Esterification stage: PTA, trimesic acid or pyromellitic acid and ethylene glycol EG are weighed according to the acid-alcohol molar ratio of 1:1.3-1.5, and are put into the reactor together with the catalyst and the heat stabilizer to carry out the esterification reaction under the protection of nitrogen. The reaction conditions are: reaction temperature 230-250℃, pressure 0.25-0.4Mpa, and the temperature at the top of the fractionation column is controlled at 110-135℃. The reaction ends when the water output reaches 93-95% of the theoretical water output, and the pressure is released to prepare for the ester exchange stage. Transesterification stage: after the pressure of the reactor is released to normal pressure, the pre-weighed hydroxyl-terminated polyphenylene ether is put into the reactor, nitrogen is added to adjust the pressure of the reactor, and the transesterification reaction begins. The reaction temperature is 230-250°C, the pressure in the reactor is 0.25-0.4Mpa, and the temperature at the top of the fractionation column is 110-135°C. When the reaction water output reaches more than 97% of the theoretical water output, the pressure is released to prepare for the polycondensation stage. Polycondensation stage: after the pressure of the reactor drops to normal pressure, vacuumization is started for polycondensation reaction, the vacuum degree is 20~60Pa, and after the discharge power reaches the predetermined value of 200W~250W of the stirring power setting value of the 80L reactor, the polycondensation reaction is completed, and the vacuum discharge is removed and granulated to prepare hyperbranched polyester-polyphenylene ether functional masterbatch; The prepared functional masterbatch has a melt viscosity of 3~20Pa×S and a melting temperature of 210℃~260℃; (2) Preparation of modified wholly aromatic liquid crystal polyester and its fiber: The hyperbranched polyester-polyphenylene ether functional masterbatch prepared above and the conventional spinning-grade fully aromatic LCP liquid crystal polyester resin are mixed in a certain proportion after vacuum drying to obtain a blended modified slice, and then the blended modified slice is melt-spun by a single-screw and double-screw spinning machine to obtain a fully aromatic liquid crystal polyester fiber that is conducive to PPO resin compounding. The specific process parameters are as follows: The drying temperature of polyester-polyphenylene ether masterbatch is 80℃~110℃, the vacuum degree is 10~30Pa, and the drying time is 12~24 hours; the drying temperature of aromatic LCP resin is 100℃~130℃, the vacuum degree is 10~30Pa, and the drying time is 8~12 hours; Blended chip spinning process: spinning machine screw temperature 260~360℃, spinning die head temperature 260~360℃, drafting roller temperature 70~120℃, spinning tunnel temperature 150~250℃, metering pump frequency 10~50HZ, spinning speed 500m / min~2000m / min, drafting multiple 1.0~1.5 times.
Citation Information
Patent Citations
Low-dielectric high-strength resin composition and prepreg and laminated board prepared from same
CN113185828A
Liquid crystal polyester fiber and preparation method thereof
CN106592002A
Wholly aromatic liquid crystal polyester resin and application thereof
CN111072936A